The Effects of Krill Oil Content on Asthma - Jemima Lewi Santoso; Anna Lewi Santoso (Green Publisher Indonesia, 2024)
Asthma is a lung disease that is increasing in the number of patients and whose severity is difficult to control. Various single antioxidants have been studied to reduce the severity and period of asthma exacerbations but the appropriate intervention compound has yet to be found. Krill oil contains various kinds of antioxidant compounds at high levels. Objective: To explain the effect of the antioxidant compounds in krill oil on asthma. Research Methods: Several journals and articles examined the effects of each antioxidant compound in krill oil on asthma. Results: several studies have shown that the effects of antioxidant compounds in krill oil can reduce inflammation and exacerbations of asthma. Conclusion: Biomolecular research is needed to determine the levels of antioxidant compounds in krill oil considering that the composition of krill oil can easily change due to various factors.